Association of lung function with functional limitation in older adults: A cross-sectional study. - Yu Gao (Public Library of Science (PLoS), 2021)
Introduction Impaired lung function is independently associated with higher rates of disability, however, few studies have examined the association between lung function and functional limitation. This study aimed to assess this association and dose-response relationship in older adults. Methods Data from the National Health and Nutrition Examination Survey (2007-2012) was used as a cross-sectional study. Lung function was determined by Forced expiratory volume in 1 second (FEV1) and forced vital capacity (FVC). Functional limitation in older adults was identified by six self-reported questions on physical function. 3070 adults aged 60 and over were enrolled in our study. Logistic regression models and restricted cubic spline models were applied to examine the association between lung function and the risk of functional limitation. Results FEV1 and FVC were inversely associated with the risk of functional limitation. In the full adjusted model, compared with the lowest tertile of FEV1, the odds ratios (95% confidence intervals) of functional limitation for tertile 2 and tertile 3 were 0.5422 (0.3848-0.7639) and 0.4403 (0.2685-0.7220), and the odds ratios (95% confidence intervals) of functional limitation for tertile 2 and tertile 3 of FVC were 0.5243 (0.3503-0.7848) and 0.3726 (0.2072-0.6698). Furthermore, an inverse association persisted after stratified analysis by gender and sensitivity analysis. Dose-response analyses showed that the odds of functional limitation declined with increase in FEV1 and FVC in a nonlinear manner. Conclusions Lung function was inversely associated with functional limitation among older adults.